2021
DOI: 10.1371/journal.pone.0250210
|View full text |Cite
|
Sign up to set email alerts
|

Effects of light spectrum on morpho-physiological traits of grafted tomato seedlings

Abstract: It is already known that there are many factors responsible for the successful grafting process in plants, including light intensity. However, the influence of the spectrum of light-emitting diodes (LEDs) on this process has almost never been tested. During the pre-grafting process tomato seedlings grew for 30 days under 100 μmol m-2 s-1 of mixed LEDs (red 70%+ blue 30%). During the post-grafting period, seedlings grew for 20 days under the same light intensity but the lightening source was either red LED, mix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Plants exposed to a mixture of red and blue light had greater photoreceptor excitation, like phytochromes, cryptochromes, and phototropins, and had higher photosynthetic activity than plants exposed to monochromatic red or blue light 46 . According to Yousef and coauthors showed that a combination of R and B LED light with a high R portion was effective in producing vigorous grafted tomato seedlings compared to blue and red light alone 20 , 47 , 48 . Also, Dong et al 49 , as compared to blue light alone, red light alone, and sunshine, combined red and blue light (1/3 blue light at 450–460 nm + 2/3 red light at 620–630 nm, at 400 lx and 12 h photoperiod for 60 days) improved the DW and bio efficiency of Cordyceps militaris mushroom.…”
Section: Discussionmentioning
confidence: 99%
“…Plants exposed to a mixture of red and blue light had greater photoreceptor excitation, like phytochromes, cryptochromes, and phototropins, and had higher photosynthetic activity than plants exposed to monochromatic red or blue light 46 . According to Yousef and coauthors showed that a combination of R and B LED light with a high R portion was effective in producing vigorous grafted tomato seedlings compared to blue and red light alone 20 , 47 , 48 . Also, Dong et al 49 , as compared to blue light alone, red light alone, and sunshine, combined red and blue light (1/3 blue light at 450–460 nm + 2/3 red light at 620–630 nm, at 400 lx and 12 h photoperiod for 60 days) improved the DW and bio efficiency of Cordyceps militaris mushroom.…”
Section: Discussionmentioning
confidence: 99%
“…Naznin, et al 38 and Yang, et al 39 investigated in pepper seedlings and Yang et al 40 tomato seedlings, and they found that in particular the red LED light was important for producing strong seedlings. Also, Yousef and coauthors showed that a combination of R and B LED light with a high R portion was effective in producing vigorous grafted tomato seedlings 28 , 29 . In most studies a combination of R and B light was more effective in promoting plant growth and development than the use of one LED source alone.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, among environmental factors, the role of light quality on mediating seedling growth and vigor is currently the most neglected one [ 8 , 9 ]. This topic has been currently addressed by a handful of studies, where different light quality regimes were reported for driving optimal growth during healing and acclimatization [ 5 , 6 , 10 ]. For instance, monochromatic red (R) light led to optimum grafted tomato seedling quality [ 5 ], whereas a spectrum including both blue (B) and R spectral regions was required in pepper [ 6 ].…”
Section: Introductionmentioning
confidence: 99%